Determination of 14 Polycyclic Aromatic Hydrocarbons in Mainstream Smoke from Flue-Cured Cigarettes by GC-MS Using a New Internal Standard - Xie, Yueqin; Tong, Hongwu; Yan, Xiangyang; Yang, Xiaoping; Ding, Bin; Liu, Shaomin (Asian Journal of Chemistry, 2012)
A method for the determination of 14 polycyclic aromatic hydrocarbons in cigarette mainstream smoke using 1,2-bis(9-anthryl)ethane as an internal standard has been developed and was applied to the analysis the Chinese cigarettes. The analytical method involves an ultrasonic extraction of Cambridge filters with cyclohexane followed by a solid-phase extraction on a Si cartridge for cleanup. After being concentrated, the samples were directly injected for gas chromatographymass spectrometry detection. The mainstream smoke from the flue-cured cigarettes had individual polycyclic aromatic hydrocarbons ranging from benzo[k]fluoranthene at levels below 3.0 ng cig-1 to phenanthrene at levels of around 160 ng cig-1 . The polycyclic aromatic hydrocarbon levels varied among the different cigarette brands, with the amount of the total 14 polycyclic aromatic hydrocarbons ranging from 0.67 µg cig-1 to 0.80 µg cig-1. Moreover, we compared levels of polycyclic aromatic hydrocarbons in mainstream smoke with phytosterols in tobacco of cigarettes. The results indicated that the free phytosterols were highly correlated with total polycyclic aromatic hydrocarbons (r = 0.952, P < 0.001) and carcinogenic polycyclic aromatic hydrocarbons (r = 0.977, P < 0.001).